Media Arts as a Medium of Urban Cultural Reproduction: The Case of Malang as a UNESCO Creative City - Linda Lestari; Vicky Arief Herinadharma; Eli Jamilah Mihardja (Asosiasi Dosen Muda Indonesia, 2026)
The designation of Malang as part of the UNESCO Creative Cities Network in the Media arts category in 2025 marks a significant milestone in strengthening the city’s identity rooted in creativity. This study aims to analyze the role of media arts as a medium for the reproduction of urban culture in the context of Malang as a global creative city. The study employs a qualitative approach using a case study design. Data were collected through participatory observation, in-depth interviews with media arts practitioners and creative communities, as well as an analysis of documents related to policies and activities within the city’s creative ecosystem. Data analysis was conducted using a thematic-interpretive approach based on Walter Benjamin’s theory of the reproduction of works of art, which highlights the concepts of aura, technical reproducibility, the shift in the value of art from cult value to exhibition value, and the democratization of cultural access through reproductive technologies. The research findings indicate that media arts in Malang City function not only as technology-based artistic practices but also as a medium that represents and reproduces the city’s cultural identity through symbols, narratives, and the social experiences of its community. The development of digital technology enables media art works to be produced, exhibited, and widely distributed through digital platforms, thereby expanding public access to creative works. These findings affirm that media arts play a crucial role in the reproduction of the city’s culture while reinforcing Malang’s identity as a creative city within the global network.